PEMETAAN CAKUPAN DAYA PANCAR SINYAL GSM 2G TELKOMSEL DI KOTA MANOKWARI MENGGUNAKAN ANALISIS SIG - Dwi Safitri; Abdul Muis Muslimin; Rosalina R Mirino (Jurnal Natural, 2018)
A study has been conducted on evaluating the coverage signals transmitting power of BTS Telkomsel in the city of Manokwari using geographic information system analysis. This study aims to analyze the coverage of the signal transmitting power of each BTS Telkomsel in the study area based on the residential and administrative variables, by determining the slope shadow area using 3-dimensional analysis and mapping the coverage of Telkomsel's cellular network in Manokwari Regency with the analysis method of Geographic Information System (GIS). From the study, Telkomsel GSM 2G signal coverage map was obtained based on residential variables, the area covered by the signal is in West Manokwari District around 99.78% covering an area of 9.3 km2, in East Manokwari District around 96.24% covering 2.05 km2, At South Manokwari District around 12.3% covering 0.81 km2 and in North Manokwari District there is no residential area covered by the signal. Based on administrative boundaries, the area of ​​the district covered by GSM 2G Telkomsel is obtained, in West Manokwari District around 64% covering an area of 41.1 km2, in East Manokwari District around 80% covering 15 km2, in South Manokwari District around 50.31% covering 3.7 km2 and in North Manokwari District which is about 4% covering 1.2 km2. With the 3-dimensional analysis method it can also be seen that the slope shadow area that is not reachable by Telkomsel's 2G GSM signal. From the results of data processing, a slope shadow area with an area of ​​0.2 km2.